Extending evidence-based dentistry beyond clinical trials: implications for materials research in endodontics - Jason Wong (Universidade Estadual de Campinas, 2015)
Evidence-based dentistry is an emerging perspective to insure that the best available research evidence is integrated in clinical practice for the maximal benefit of each individual patient. It is focused on identifying the statistically and clinically significant findings from randomized trials. The successful practice of dentistry relies on a vast spectrum of dental research, which ranges from materials research to observational studies. This is particularly true in the domain of endodontics. Therefore, there is a need to expand the traditional domain of evidence-based dentistry to materials research.Here, we describe an approach to obtain a preliminary systematic review of the research literature on the efficacy and efficiency of mineral trioxide aggregate (MTA) for sealing and repairing furcal perforations. Examination of the pertinent MTA literature identified eight journal articles that met fundamental criteria of published research studies of efficacy of MTA over other materials for use as a furcation repair material. Taken together, seven among these reports (88%) were found to generate evidence that could be considered reliable and acceptable from the viewpoint of evidence-based (EB) endodontic dental practice. A critical synthesis of this evidence is discussed.